Gender Reassignment Procedure in Spain a Field of Abuse and Circumvention (Discourse of Law and Administration, 2026)
Spain in age aspects is a very liberal country, one of these aspects is the approach to gender reassignment. In 2023, after 15 years of the 2007 law, there has been a change in this area. Nowadays, the gender reassignment procedure has been extremely simplified. This simplification has also become, as specific case studies show, not only a field for abuse of the law in specific cases, but also a systemic threat due to statistics. These clearly show that this right is used far more frequently by men. In view of the above, it will first be pointed out why the law hitherto in force no longer meets social and legal expectations, the current procedure for gender reassignment will also be presented, and finally the article will point out the areas that give rise to legal and social pathology in this area. The theoretical-legal and dogmatic-legal method will be used in the deliberations.
Keywords: gender reassignment; gender reassignment procedure; abuse of the law; LGBTIQ rights